Solvent-dependent fluorescence behaviour of imide-fused [n]phenacenes (n = 3, 5, 7). Issue 6 (30th January 2023) - Nose, Keito; Yoshioka, Kaito; Yamaji, Minoru; Tani, Fumito; Goto, Kenta; Okamoto, Hideki
Abstract : Imide-fused [ n ]phenacenes were synthesised and their fluorescence spectra were observed to reveal that they showed positive solvatofluorochromism due to intramolecular charge transfer from the phanacene π core to the imide moieties in the S1 state. Abstract : Imide-fused [ n ]phenacenes ( n PDI s, n = 3, 5, 7) were systematically synthesised and their electronic features were investigated by electrochemical and electronic spectral measurements. n PDI s showed two reduction waves attributed to formation of radical ions and dianions. 3PDI produced blue fluorescence independent of solvent polarity. In contrast, 5PDI and 7PDI displayed marked positive solvatofluorochromism due to intramolecular charge transfer characters between the imide moieties and phenacene π cores in the excited state. The spectral features were analyzed by the Lippert–Mataga relationship and theoretical calculations.